2022
DOI: 10.1186/s12951-022-01584-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived small extracellular vesicles: potential roles and mechanism in glioma

Abstract: Small extracellular vesicles (SEVs) are extracellular vesicles containing DNA, RNA, and proteins and are involved in intercellular communication and function, playing an essential role in the growth and metastasis of tumors. SEVs are present in various body fluids and can be isolated and extracted from blood, urine, and cerebrospinal fluid. Under both physiological and pathological conditions, SEVs can be released by some cells, such as immune, stem, and tumor cells, in a cytosolic manner. SEVs secreted by tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 155 publications
0
24
0
Order By: Relevance
“…Lower miR-375 levels were also typical for vesicles from peripheral blood of GBM patients and correlated with poor prognosis ( Xu et al, 2021b ). MiR-944 could define tumor malignancy as high-grade gliomas express lower levels of miR-944 and correlate with lower overall survival of patients ( Jiang et al, 2021 ; Guo et al, 2022 ). PD-L1 + vesicles were also found in peripheral blood and PD-L1 level was positively correlated with tumor size ( Shenoy et al, 2021 ; Vautrot et al, 2021 ).…”
Section: Extracellular Vesicles In Diagnostic and Prognosis Of Gbmmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower miR-375 levels were also typical for vesicles from peripheral blood of GBM patients and correlated with poor prognosis ( Xu et al, 2021b ). MiR-944 could define tumor malignancy as high-grade gliomas express lower levels of miR-944 and correlate with lower overall survival of patients ( Jiang et al, 2021 ; Guo et al, 2022 ). PD-L1 + vesicles were also found in peripheral blood and PD-L1 level was positively correlated with tumor size ( Shenoy et al, 2021 ; Vautrot et al, 2021 ).…”
Section: Extracellular Vesicles In Diagnostic and Prognosis Of Gbmmentioning
confidence: 99%
“…Size-exclusion chromatography and immunoaffinity capture are the most promising methods for clinical application. As described above, the usage of immunoaffinity capture is limited by absence of the data about specific GBM-markers and impossibility to remove antibodies ( Guo et al, 2022 ). So, specific GBM EVs surface markers are still needed to be defined and selected carefully.…”
Section: Extracellular Vesicles In Diagnostic and Prognosis Of Gbmmentioning
confidence: 99%
“…A study by Lin et al revealed that EndoMT in endothelial cells is also promoted by tumor‐associated macrophages (TAMs) by secretion of CCL18 under the influence of TGF‐β and Notch signaling pathways (Lin et al, 2015). Tumor‐derived small extracellular vesicles (TEX), in patients suffering from cancer are an important intercellular communication and function mechanism, and TGFβ is one of the major components of TEX (Guo et al, 2022; Ludwig et al, 2022). TGFβ + —tumor‐derived small extracellular vesicles (TEX) are seen to activate macrophage chemotaxis without a shift in M1/M2 phenotype, these activated macrophages reprogrammed their activities to a proangiogenic phenotype with significantly increased proangiogenic factors and functions (Ludwig et al, 2022).…”
Section: Tgf‐β—acting As a Proto‐oncogenementioning
confidence: 99%
“…Exosomes are endosomal membrane-derived vesicles, approximately 50–150 nm in size, formed during endocytosis and secreted by almost all types of cells, and are present in large numbers in body fluids such as blood, urine, cerebrospinal fluid, tears, and saliva. Their main constituents are lipids, proteins, and nucleic acids, including microRNAs (miRNAs), messenger RNA (mRNA), and DNA derived from secretory cells transferred to other cells [ 12 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ,…”
Section: Introductionmentioning
confidence: 99%